Homogenization or diversification? The impact of globalization on cultural identity of the first and second-generation immigrants - Bouymaj, I.; Pereira, R. (Journal of Globalization Studies, 2022)
Globalization's accelerating influence has been at the forefront of the debate on the potential ramifications of cultures' homogenization. Research has shown that with the increased migration, the world is becoming more multiculturally diverse, nonetheless more homogenized. This study aims at determining if globalization has positively impacted the participants'cultural identities and lives and examines if this phenomenon leads to the homogenization of cultures. An ethnographic study was conducted on 32 participants from the first and second-generation migrants, originating from 21 countries, to depict globalization's real impact on their cultural identities and lives. The research used a qualitative approach based on structured interviews and employed the content analysis methodology for interpretation. The findings of the research questions revealed that, for the most part, globalization has, in fact, positively impacted individuals' cultural identities and lives. The positive effect of globalization appeared in the form of increased education and employment opportunities and increased open-mindedness regarding cultural diversity. The study also rejected that the world has become more homogenized, but rather that globalization has opened the doors to the enhancement of cultures.